THE EFFECT OF ROUNDTABLE TECHNIQUE ON STUDENTS LEARNING OUTCOMES IN WRITING DESCRIPTIVE TEXT OF GRADE TEN AT SMA NEGERI 4 SIGI - Nurhaliza Zahwalia; Sriati Usman; Erniwati; Budi (Universitas Muhammadiyah Makassar, 2026)
This research aimed to investigate the effect of the Roundtable Technique on students’ learning outcomes in writing descriptive text of grade ten at SMA Negeri 4 Sigi. A quantitative methodology was employed, incorporating a quasi-experimental design featuring pre-test and post-test control groups. The population comprised tenth-grade students at SMA Negeri 4 Sigi, with samples chosen via cluster random sampling. Class X A served as the experimental group, instructed through the Roundtable Technique, whilst Class X C functioned as the control group, getting traditional instruction. Writing evaluations were administered prior to and subsequent to the intervention. The mean pre-test score for Class X A was 33.33, whereas Class X C achieved a score of 40.21. Following treatment, the experimental group's mean score rose to 80.42, while the control group's score attained 59.26. The calculated t-counted was 6.03, exceeding the t-table of 2.02, signifying a statistically significant difference. The results indicate that the Roundtable Technique had a significant effect on students’ learning outcomes in descriptive writing. It encouraged students to be more engaged, collaborative, and confidents in developing ideas, using vocabulary, and applying grammar. The technique is recommended to enhance students’ skills in writing descriptive texts.